2021
DOI: 10.18060/25273
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Pandemic Teaching: Emergency Remote Teaching and Learning and English Learner Teachers

Abstract: The purpose of this study is to illuminate how English Learner (EL) teachers in the Great Lakes region responded to the sudden shift to emergency remote teaching and learning (ERTL) at the onset of COVID-19 school closures in March 2020. Using an online survey, we examined how EL teachers from Indiana, Minnesota, and Wisconsin continued legal provisions of instruction and service through the end of the 2019-2020 school year. We look closely at the state of Indiana, a state with a more recent immigrant populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The bulk of this two‐part study is focused on our interview findings, but we discuss responses from a three‐state survey on the provision of instruction and service before and during ERTL to foreground the study (Benegas et al., 2021; Cushing‐Leubner et al., 2021; Morita‐Mullaney et al., 2021). Survey results from this study clearly demonstrated the distinctions between instruction and service pre‐pandemic and during ERTL.…”
Section: Survey Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bulk of this two‐part study is focused on our interview findings, but we discuss responses from a three‐state survey on the provision of instruction and service before and during ERTL to foreground the study (Benegas et al., 2021; Cushing‐Leubner et al., 2021; Morita‐Mullaney et al., 2021). Survey results from this study clearly demonstrated the distinctions between instruction and service pre‐pandemic and during ERTL.…”
Section: Survey Findingsmentioning
confidence: 99%
“…For example, EL teachers facilitate home/school communications or transportation (Harvey & Teemant, 2012). Service may also include acquiring internet service or connecting youth and families to health and human services (Benegas, Morita‐Mullaney, Cushing‐Leubner, Stolpestad, & Greene, 2021; Cushing‐Leubner, 2021; Morita‐Mullaney, Greene, Cushing‐Leubner, Stolpestad, & Benegas, 2021). These roles of instruction and service took on new dimensions during ERTL and how EL teachers self‐positioned or were positioned by others contributes to how language teacher identity (LTI) forms.…”
mentioning
confidence: 99%